Developing The Organization Integration Through Problem/Solution Tree: A Case Study of EPC Solar Panel Company - Widodo, Tabita Emmanuella; Smatupang, Togar Mangihut; Kembaren, Pennoh Philips (PT. EQUATOR SINAR AKADEMIA, 2025)
Rapidly growing based on the company’s revenue, the scale and number of projects that have been increased every year, the margin of each project has gap that does not meet with the targeted plans. Projects most of the time are over budget, delayed, and company can’t identify the risk management they faced from the calculation, construction, until the after-service. ATW has identified these circumstances as challenges to be mitigate. Based on sums of all the projects budget in Q2 in 2024, the highest activities that overbudget compared to the planning is Installation by 74.6%. Compared to the initial budget, the installation cost nearly double. The company want to know what cause the gap of over budget and uncontrollable additional cost and how to improve the budgeting. With Problem and Solution Trees to understand the root caused and the solution, this research explores problems that related to projects to perceive the essentials. Developing Organizational Integration for the company related to organization, project, and cross-departments. Based on the Problem and Solution Tree, the causes are unintegrated and uncoordinated system, lack of standardize procedure, and miss communication in projects. Meanwhile, the system model is organizational integration where will improve the gaps with integrating the cross department and make it sustain for evaluating the closing project. This research’s aim is for the expenses to be controlled and monitored to gain the margin and for the company to expand the business.